ANTIBACTERIAL ACTIVITY TESTING OF MUSSEL EXTRACT (Polymesoda erosa) AGAINST Staphylococcus aureus and Escherichia coliBACTERIA - Jeremy Chrisdwi Putra Hutajulu; Rahman Karnila; Edison Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTThis study aims to determine the antibacterial activity of mussel extract (Polymesoda erosa) against Staphylococcus aureus and Escherichia coli bacteria, yields and bioactive compounds. The treatment given was the extraction of mussels with different solvents consisting of hexane, ethyl acetate and methanol. Parameters observed were yield, bioactive compounds and antibacterial activity. The yield value of mussel shell extract with hexane solvent was 0.8653%, ethyl acetate solvent was 0.9968%, and methanol solvent was 1.9497%. The bioactive compounds found in the hexane extract are steroids; in the ethyl acetate extract are alkaloids, steroids, flavonoids, saponin, and phenolic; meanwhile in the methanol extracts are alkaloids, steroids, flavonoids, saponin, and phenolic. Mussel extract had an antibacterial activity with formation of inhibition zone, wherein in hexane 14,06 mm (strong) of S. aureus and 19,13 mm (strong) of E. Coli, in ethyl acetate 19,54 mm (strong) of S. aureusand 21,78 mm (strong) of E. Coli, and in methanol extraction obtain 22,62 mm (very strong) of S.aureus and 25,80 mm (very strong) of E.coli. Keywords: Bioactive compounds, antibacterial activity, mussel shells (Polymesoda erosa)